Analysis of Community Satisfaction of Pacarkembang Village Reviewed from the Ease, Speed and Effectiveness of the KNG (Klampid New Generation) Application - Dita Ken Kariera (International Journal of Social, Economic, and Business, 2025)
This study aims to analyze the level of community satisfaction with the use of the Klampid New Generation (KNG) application as an innovation in digital population administration services in Pacarkembang Village, Surabaya. Using a descriptive quantitative approach with 244 respondents, this study examined the effect of service speed, ease of use, and effectiveness of document completion on public satisfaction. The results of the analysis showed that simultaneously the three variables had a significant effect on community satisfaction with an R² value of 76.3%. Partially, only the variables of service speed and effectiveness had a significant effect, while ease of use did not. However, all variables have high average values that indicate user satisfaction. These findings confirm the importance of improving speed and effectiveness in digital services. It is suggested that the development of the KNG application be focused on improving system performance and training for the community so that the benefits are more optimal.